GRAPHITE-CONTAINING FIRE-RESISTANT BRICK FOR REFINING MELTED METAL - HAYAMA KIYOHISA (1993)
PURPOSE:To provide the subject brick especially useful as a furnace material for refining stainless steel, extremely low carbon steel, etc. CONSTITUTION:The objective brick is characterized by containing 5-80wt.% of a fireresistant raw material obtained by calcining or electrically melting 20-90wt.% of MgO, 5-80wt.% of Cr2O3, <= 10wt.% of SiO2, <=20wt.% of Al2O3 and <=20wt.% of Fe2O3, and further containing 3-30wt.% of graphite and 15-90wt.% of MgO as the remaining components. Thereby, this brick has excellent corrosion resistance, does not cause the formation of an opening at a sealing part between the bricks, exhibits an extremely smooth dissolution damage shape and has excellent spalling resistance. The properties permit that the brick is useful as a furnace material for refining stainless steel, extremely low carbon steel, etc., which require lining materials especially lowered in the carbon contents.